If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 10 = 14x + -10 Reorder the terms: 10 + 12x = 14x + -10 Reorder the terms: 10 + 12x = -10 + 14x Solving 10 + 12x = -10 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 10 + 12x + -14x = -10 + 14x + -14x Combine like terms: 12x + -14x = -2x 10 + -2x = -10 + 14x + -14x Combine like terms: 14x + -14x = 0 10 + -2x = -10 + 0 10 + -2x = -10 Add '-10' to each side of the equation. 10 + -10 + -2x = -10 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = -10 + -10 -2x = -10 + -10 Combine like terms: -10 + -10 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 2+1.8r=-1.96 | | 263-y=148 | | 15x+90+17=25x-13 | | 15x+90+17=25x | | 4-16=2x+6x | | 3x+9=2Y+1 | | (x-4)+(2x+1)=0 | | -23/10=-0.5x-3 | | 4=6/5v | | 15(x+6)=x | | 3y^2+2y-20=0 | | x/4-8-10 | | 10x-15=5x+30 | | 0.75+0.5p=-0.5 | | x/5=6/7 | | y-20=-19 | | lnx=-10.56 | | 6*-2-6*4= | | e^2=y | | (x/3)-510 | | 15-18n=27 | | -6t(-7)=17 | | 3+4=25 | | 3(1x+4)=2(1x-1) | | 12(4+n)+5(-2x-9)=18 | | 3+4*7+1=35 | | 15f-2-(4-36)-5000-2-41-(69189)= | | -5=x+-9 | | 6+6y+4t-y-t-12= | | -5=6+-9 | | 4x+55=-8 | | f(x)=x+x(5) |